2022
DOI: 10.1002/mop.33203
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen detection system based on TDLAS–WMS and a compact multipass gas cell

Abstract: In this paper, a sensitive oxygen monitoring system was demonstrated using tunable diode laser absorption spectroscopy and wavelength modulation spectroscopy. Light from a distributed feedback laser near 760.8 nm was coupled into a compact Herriott cell with a 3.3 m optical path. A LabVIEWbased orthogonal lock-in amplifier was developed to extract the gas concentration information from the absorption signal, which can achieve baseline fitting, background deduction, filtering, and harmonic extraction. Oxygen me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Although the K‐type thermocouple can be used to measure temperature accurately, its reliability and suitability may decrease when gas concentration is low because of the low sensitivity of the DAS. Therefore, we explored the possibility of using WMS and WMS‐2f/1f to measure temperature, which have higher sensitivity than DAS 2,14 …”
Section: Results and Analysismentioning
confidence: 99%
“…Although the K‐type thermocouple can be used to measure temperature accurately, its reliability and suitability may decrease when gas concentration is low because of the low sensitivity of the DAS. Therefore, we explored the possibility of using WMS and WMS‐2f/1f to measure temperature, which have higher sensitivity than DAS 2,14 …”
Section: Results and Analysismentioning
confidence: 99%
“…To solve the defects of traditional methods in measuring CH4 gas concentration in pipelines, Yao Wang developed a TDLAS-based instrument for measuring CH4 concentration directly by pipeline laser [21]. Jvqiang Chang et al developed an oxygen monitoring system based on WMS-TDLAS, and the Allan variance revealed that limit of detection (LOD) of this equipment was 0.247% [22]. Weilin Ye et al introduced a CH4 measurement system based on TDLAS and LabVIEW, which used hard threshold, Coif5 wavelet basis and Heursure rule to effectively reduce the high-frequency noise of the sensor, and the minimum detection limit (MDL) of 1σ is 23.68 ppbv [23].…”
Section: Gas Detectionmentioning
confidence: 99%
“…Zhang et al used a commercial laser controller (CLD1015, Thorlabs), lock-in amplifier (LIA-MV-200-H, FEMTO Messtechnik GmbH, Berlin, Germany), and industrial computer (PCM-3365, Advantech Technology, China) to measure CO 2 using a TDLAS system [ 14 ]. Chang et al developed an oxygen detection system using a laptop equipped with a DAQ card (USB-6211;NI) and a LabVIEW software platform [ 28 ]. In addition, the study of miniaturized multi-pass cells (MPCs) can also improve the integration of the system [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%